El francés como lengua franca de la Unión Europea: luces y sombras de una estrategia fallida - FERNÁNDEZ VÍTORES, David (Revista de Filología Románica, 2010)
At the beginning of the European Community, when there were only four official languages, French enjoyed a privileged position in terms of institutional use as a lingua franca. However, this situation changed dramatically with the entry of United Kingdom in the Community club and the subsequent incorporation of English into the repertoire of official languages of the European Union. The purpose of this paper is to describe this process of change and explain the strategies adopted by France in order to preserve the dominant position of French in the Community. It analyzes language policies implemented so far in defense of French, both inside and outside France, and evaluates the success or failure of those in an enlarged Union with 23 official languages.